PENGARUH BUDAYA ORGANISASI DAN ROTASI PEKERJAAN TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI PUSKESMAS DI KOTA TARAKAN - Rozi Djoko Arfiono; Nurul Hidayat; Isfarudi (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study aims to determine the effect and analyze the influence of organizational culture and job rotation on work motivation and performance of Public Health Center employees in Tarakan City. . The total population is 215 people and the sample is 85 people. Data collection by distributing questionnaires and continued in the analysis by path analysis. The results of hypothesis testing have proven that organizational culture has a significant effect on the work motivation of Puskesmas employees in Tarakan City, this indicates that every change in organizational culture that is better will have a positive impact on the desire of employees to be more enthusiastic at work. Job rotation has a significant effect on employee work motivation, with this indicating that every job rotation policy can be carried out in every certain period, giving employees more incentive to work harder because of the new position as a result of the rotation. Organizational culture directly has a significant effect on employee performance, this indicates that any increase in the existing organizational culture will have a positive impact on employee performance. Job rotation directly has a significant effect on employee performance, this indicates that job rotation policies are often carried out and proper placement can improve employee performance. Work motivation has a significant effect on employee performance, this indicates the higher employee work motivation will improve performance, and vice versa. The direct influence between organizational culture and job rotation on employee performance is greater than the indirect effect between organizational culture and job rotation through work motivation so that the direct effect is more dominant than the indirect effect. Work motivation does not fully partially mediate the influence of organizational culture and job rotation on employee performance is greater than the indirect influence between organizational culture and job rotation through work motivation so that the direct influence is more dominant than the indirect effect. Good organizational culture and job rotation as well as motivation that is still monitored for its implementation will be able to influence employee performance to be better.